Relative abundance of insect species in oil palm - cocoa intercrop at Kusi in the Eastern Region of Ghana - Bawa, A.S.; Yawson, G.K.; Ofori, S.E.; Appiah, S.O.; Afreh-Nuamah, K. (INTERNATIONAL RESEARCH JOURNALS, 2011)
Insect species of sole oil palm, sole cocoa and oil palm cocoa intercrop was studied at the CSIR-Oil Palm Research Institute; on plot K4 while cocoa monocrop at a farm on the boundary of the Institute’s plantation at Kusi, in the Eastern Region of Ghana. The objective was to identify the occurrence and relative abundance of these insect species in oil palm-cocoa intercrop to compare these insects with existed ones in oil palm and cocoa monocrops over a period of six months (September 2008 to February 2009). Chemical knockdown application method by fumigation was employed to collect insect. An area 0.5 ha plot each was demarcated for the treatments; i.e oil palm monocrop, cocoa monocrop and oil palm-cocoa intercrop. The oil palm and cocoa plantations were 29 years and 21 years respectively. Vinyl sheets measuring 2.8 X 8 m each were placed beneath the selected trees for the insect collection, and the trees were hot-fogged early in the morning between 5:00–7:30am with Plan D EC25 insecticide (Deltamethrin 25g active ingredient/L) at a rate of 20ml insecticide/ 4.5 l of diesel using a Puls FOG machine (K-10SP). Results showed that relatively more insects occurred in the oil palm-cocoa intercrop compared to the oil palm and cocoa monocrops. Insect species belonging to six orders were collected as follows; Hymenoptera (12), Coleoptera (30), Diptera (10), Hemiptera (6), Thysanoptera (1) and Orthoptera (1). Oecophylla longinoda Latr. was the dominant insect species in studied plots. There were more beneficial insect species (predators and parasitoids) in the intercrop when compare to the monocrops. There were significant differences (p < 0.001) in the number of insect species between cocoa monocrop and oil palm monocrop, similarly oil palm monocrop and oil palm-cocoa intercrop. However there was no significant difference (p > 0.001) species between cocoa monocrop and oil palm-cocoa intercrop. The study revealed that the two crops do not have common insect pests and in association will not compound insect pests problem of either crop.
Keywords: Sole oil palm; Sole cocoa; oil palm - cocoa intercrop; insect species